The history and mystery of sacubitril/valsartan: From clinical trial to the real world - Zhang, Mingsong; Zou, Yifei; Li, Yangxue; Wang, He; Sun, Wei; Liu, Bin (Frontiers in Cardiovascular Medicine, 2023)
Heart failure is a serious threat to human health, with morbidity and mortality rates increasing despite the existence of multiple treatment options. Therefore, it is necessary to identify new therapeutic targets for this disease. Sacubitril/valsartan is a supramolecular sodium salt complex of the enkephalinase inhibitor prodrug sacubitril and the angiotensin receptor blocker valsartan. Its combined action increases endogenous natriuretic peptides while inhibiting the renin-angiotensin-aldosterone system and exerting cardioprotective effects. Clinical evidence suggests that sacubitril/valsartan is superior to conventional renin-angiotensin-aldosterone inhibitor therapy for patients with reduced ejection fraction heart failure who can tolerate angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers. The therapy reduces the risk of heart failure hospitalization, cardiovascular mortality, and all-cause mortality and has a better safety and tolerability record. This review describes the potential pathophysiological mechanisms of cardiomyocyte injury amelioration by sacubitril/valsartan. We explore the protective effects of sacubitril/valsartan and outline the therapeutic value in patients with heart failure by summarizing the results of recent large clinical trials. Furthermore, a preliminary outlook shows that sacubitril/valsartan may be effective at treating other diseases, and provides some exploratory observations that lay the foundation for future studies on this drug.